Effect of adding garlic essential oil on some properties of edible gelatin films prepared by laboratory (Damascus University Journal of agriculture sciences, 2022)
The aim of this investigation is to extract garlic essential oil (GEO), studying some different characteristics of gelatin-sodium alginate edible films which contain garlic essential oil at various final concentrations and to determine the best concentration of garlic essential oil with saving of quality characteristics of films.Garlic essential oil was prepared by steam distilling, and gelatin-sodium alginate edible films were prepared, and GEO was added by the following percentages (0.1, 0.5, 1, 1.5) %.Gelatin-sodium alginate films were tested for Moisture content (MC), Thickness, Tensile strength (), Elongation at break (EAB), Water vapour permeability (WVP), Water solubility (S), Opacity, Total phenolic content, DPPH free radical scavenging activity, Reducing power (RP), Fourier Transform Infrared Spectroscopy (FTIR), and Color parameters.Garlic essential oil negative affect on some different characteristics of gelatin-sodium alginate edible films where the results showed increased of thickness and decreased of each of tensile strength and opacity with increased concentration of added essential oil compared with control sample.Garlic essential oil positive affect on some other characteristics where the results showed decreased of each of Moisture content, Water vapour permeability, and Water solubility while increased each of Elongation at break, Total phenolic content, and Antioxidant activity with increased concentration of added essential oil compared with control sample.The results showed difference in otal color ΔE at which increased its intensity, which was expressed as ΔC.Films with (1.5 %) of garlic essential oil showed the best characteristics compared with control sample and films with (0.1, 0.5, 1) % of garlic essential oil
Keywords: garlic oil; gelatin; edible; prepared by laboratory; FTIR; DPPH